Fractionation of Serum Protein in the Indian Sheep - ADHIKARI, ALKA; MEHTA, S.P.S. (Asian Journal of Chemistry, 2010)
Fractionation of serum protein in the Indian sheep was studied. 43.295% albumin, 28.79% (α + β) globulins and 27.915% . γ-globulins were found. The observed values were compared with the earlier studies.